The protected disclosures act: reflecting on the jurisprudence of the last 10 years and the challenges ahead - Van Der Watt, Gerhardus (Centre for Law and Society, 2026)
The purpose of this paper is to reflect on, analyse and evaluate the protection offered to whistleblowers since the enactment of the Protected Disclosure Act 26 of 2000. It focuses on the Act, which seeks to combat crime and corruption through protected disclosure. It considers the fate of whistleblowers, notwithstanding the provisions provided in the Act for their protection. Globally, governments have been paying more attention to the valuable potential role of the whistleblower in preventing and disclosing fraud, corruption and other wrongdoings. This short comparative study explores the United States, selected countries within the European Union, and the three tier model of the United Kingdom, which has legislation similar to that of South Africa. Both the Protected Disclosures Act and the South African government's proposed Protection of Information Bill, or "'Secrecy Bill'," are discussed with reference to the impact on the potential whistleblower. With its 'state of the art' legislation, South Africa is at the forefront of whistleblower law worldwide. If it is understood and applied effectively, this legislation will help to deter and detect wrongdoing in the workplace, acting as an early-warning • mechanism to prevent impropriety and corruption within all work sectors.